A Survey of the place-names of the Isle of Axholme, Lincolnshire - Bullen, Kathryn Faye (2024)
The thesis comprises a comprehensive place-name survey of the Isle of Axholme, particularly of its minor names, in the style of the English Place-Name Society survey volumes. It consists of an introductory discussion of Axholme, followed by analysis of the names of major topographical features and river-names of the area, with sections of the eight parishes of Althorpe, Belton, Crowle, Epworth, Haxey, Luddington, Owston and Wroot then arranged alphabetically. This is supplemented by three appendices: an index of field- and minor names pre-1500, personal names pre-1500, and a glossary of elements and their sources for the whole corpus.